Spondylodiscitis in a 54-year-old female scuba diver. (28th March 2018) - Tuttle, Neil; Brelis, Alexandra; Brereton, Rachel; Evans, Kerrie
Abstract : A 54-year-old woman presented to a Sports Physician with a 4-year history of haemochromatosis, and she had a medical history that included a congenital spondylolisthesis resulting in a fusion of L4-S1 at age 16 years, episodic mechanical low back pain and an absence of other significant musculoskeletal symptoms. On presentation, she reported 18 months of severe low back pain that started after a scuba diving trip. After the onset of this low back pain, she developed gastrointestinal symptoms from Salmonella . The gastrointestinal symptoms improved with a course of antibiotics, but the back pain persisted in spite of analgesics, non-steroidal anti-inflammatories and several attempts at different conservative management. CT imaging ordered by the Sports Physician demonstrated an erosive spondylodiscitis of L2/3 that was not present on initial investigations. However, even in the presence of significant bony changes, the patient was successfully treated with targeted conservative therapy.